Analisis Penerapan Kriteria Green Construction pada Pelaksanaan Pembangunan Konstruksi di Kota - Selvira Purnama Karim; Arfan Usman Sumaga; Moh. Yusuf Tuloli (Transbahasa, 2024)
The rapid population growth increases the demand across various sectors, including infrastructure development. In Indonesia, infrastructure development is expected to improve public welfare, although it often significantly impacts the environment from construction to operation stages. Construction projects use limited natural resources and negatively affect the environment, such as reduced open spaces and pollution from heavy equipment and transportation. To mitigate these negative impacts, implementing environmentally friendly construction practices, known as green construction, is essential. This concept emphasizes energy efficiency, the use of eco-friendly materials, proper water management, and occupational safety. This study aims to analyze the implementation of green construction criteria in construction projects in Gorontalo City and identify the most dominant criteria applied. Data collection was conducted through surveys by distributing questionnaires to construction practitioners. Data analysis employed descriptive statistics and ranking systems. The study found that water and energy efficiency are the most dominant criteria applied, with a percentage of 80%, mainly by maximizing sunlight usage to reduce electricity consumption.